Loneliness and Social Isolation Among Older People in Northern Ireland. (16th December 2020) - Neville, Charlotte; Devine, Paula
Abstract: Loneliness and social isolation are increasingly recognised as being public health concernsparticularly in older people. Social isolation can be defined as the lack of social connections, whilst loneliness is a more subjective concept and relates to negative feelings about a lack of connections. This research explores the patterns of loneliness and social isolation of over 5, 000 people aged 50 years or over living in Northern Ireland who participated in the first wave of the NICOLA study (Northern Ireland Cohort for the Longitudinal Study of Ageing). Data were obtained by computer-assisted personal interviews and self-completion questionnaires. We focused on loneliness and social interaction, in relation to key demographic and socio-economic variables including age, gender and marital status. Key findings were that loneliness patterns varied according to gender, age, income, health and living circumstances. Future waves of NICOLA will help to longitudinally explore the effects of transition on loneliness and social isolation.